Power Factor Increase of Electric Drives of Railway Shunting Winches - Marenych, O. L.; Karzova, O. O. (Science and Transport Progress, 2021)
Purpose. The main purpose of the work is to develop recommendations for increasing the power factor of electric drives of railway shunting winches, taking into account the peculiarities of the technological process at loading and unloading sites. To achieve this purpose, the following tasks were set: to choose a rational way to increase the power factor of the electric drive of shunting winch, taking into account the peculiarities of the technological process, simplicity and reliability of the electrical circuit; develop a methodology (calculation algorithm) to determine the elements of the circuit, which are designed to increase the power factor; conduct research to determine the numerical technical characteristics of these elements, using the developed methodology; assess the power factor increase for the electric drive of some models of winches; formulate recommendations on possible modernization of the electric drive of shunting winches. Methodology. An algorithm for calculating the reactive power of an unregulated cosine capacitor, which has to be permanently connected to the terminals of a three-phase induction motor of a shunting winch drive in order to increase the power factor, is developed. Findings. Studies have shown that the proposed method of increasing the power factor gives a significant increase in different values of the load factor of the shunting winch motor, while ensuring the simplicity of the scheme and its reliability. Originality. For the first time, taking into account the peculiarities of the technology of unloading and loading cars, a method of calculating the required reactive power of an unregulated cosine capacitor, which is connected to the terminals of the drive motor, is proposed. The formula for determining the load factor of the electric motor depending on the ratio of unloaded and loaded cars that move with a winch is proposed. The formula for determining the load factor of the electric motor depending on the ratio of unloaded and loaded cars, which move using a winch is proposed. Practical value. The results are of practical value because the obtained numerical values of increasing the power coefficients of the drives of shunting winches and reactive power required for this cosine capacitors can be used as primary information in deciding whether it is advisable to modernize winch drives by connecting to the terminals of three-phase induction motor.